Preliminary Study on Delta-9-Tetrahydrocannabinol (∆9-THC): Hemispheric Lateralization with Behavioural Changes - Suliman, Noor Azuin; Mat Taib, Che Norma; Mohd Moklas, Mohamad Aris; Zakaria, Zainul Amiruddin (Journal of Science and Technology, 2014)
This study is designed inspired by the fact that there is an interhemisphere asymmetry of the brain region. A lot of researches studied in demonstrating the differences between right and left hemispheres of the brain. The objective of this preliminary study is to observe scientifically the effect of delta-9-tetrahydrocannabinol (∆9-THC) on the hemispheric lateralization with behavioural changes. Two regions of brain are selected, prefrontal cortex and hippocampus. Behavioural tests, namely heat stress test and novel-object discrimination test (NOD), were done on day seven. The hippocampus and prefrontal cortex regions of the brain were preceded to Western Blot technique in detecting c-fos. As for behavioural tests, heat stress and NOD and c-fos on hippocampus did not show significant differences. Meanwhile, the prefrontal cortex shows significant difference with p < 0.01. With these findings, reasonable dosages of ∆9-THC should be used to have statistically significant differences effects on behavioural tests.